Impact of Hospitality Industry in Poverty Alleviation in a Tourist Destination: Cross River State Scenerio - Eja, Eja .I.; Oto, Judith .E.; Yaro, Margaret .A.; Inyang, Ita .O. (Richtmann Publishing, 2011)
The geographical features of Cross River State, from the southern to the northern part; makes her a natural paradise and alsoa destination for fun seekers. These however, has necessitated towards the rapid growth of the hospitality industry especially the hotelindustry which has shown efficiency in the tourism industry in Cross River State. This paper critically examine the impact of hotelindustry in poverty alleviation in Cross River State. Data were collected in the various hotels across the three senatorial district and CrossRiver Tourism Bureau. Findings shows that out of the one hundred and twenty seven (127) hotels used for this study, only a few hotelscan afford to meet it financial obligation. This however, affect it monthly remuneration paid to the workers and employment level in theindustry. Therefore, the success of the hotel industry is rest on the various stakeholders in the industry in Cross River State.